Association between serum Vitamin E concentrations and the presence of Metabolic Syndrome: A population-based cohort study - Barzegar-Amini, Maral; khorramruz, Fateme; Ghazizadeh, Hamideh; Sahebi, Reza; Mohammadi-bajgyran, Maryam; Mohaddes Ardabili, Hossein; Tayefi, Maryam; Darroudi, Susan; Moohebati, Mohsen; Heidari-Bakavoli, Alireza; Mohammadi, Akram; Sadeghnia, Hamid Reza; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background. Metabolic syndrome (MetS) is a cluster of clinical and metabolic features that include central obesity, dyslipidemia, hypertension and impaired glucose tolerance. These features are accompanied by increased oxidative stress and impaired antioxidant defenses. Vitamin E is a major factor in the non-enzymatic antioxidant defenses. The aim of present study was to investigate the association between serum levels of vitamin E and the presence of MetS and its components in a sample population of Mashhad stroke and heart atherosclerotic disorder (MASHAD) cohort study. Methods. This cross-sectional study was carried out in 128 subjects with MetS and 235 subjects without MetS. MetS was defined according to the International-Diabetes-Federation criteria. Serum levels of vitamin E were measured using the HPLC method. Anthropometric and biochemical parameters were measured using standard protocols. Results. MetS patients had significantly lower serum levels of vitamin E (Vit E), Vit E/Total cholesterol (TC), and Vit E/ (TC+triglyceride(TG)) compared to the control group (P < 0.05). Vit E/ (TG+TC) was also significantly lower in diabetics or those with elevated levels of high sensitive C-reactive protein (hs-CRP). Additionally, there was a significant association between Vit E/ (TG + Total Cho) and the number of components of the metabolic syndrome (p= 0.02) Conclusions. There is a significant inverse association between indices of Vit E status and the presence of MetS. Moreover, a significantly lower Vit E/ (TC+TG) was observed along with individuals with increasing numbers of components of the MetS.